2017
DOI: 10.1108/ijaim-10-2016-0099
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the CEO’s characteristics on EM: evidence from Jordan

Abstract: Purpose This study aims to examine the effect of CEO’s personal characteristics on earnings management (EM) practices. Design/methodology/approach The authors use panel data for 201 non-financial companies listed on the Amman Stock Exchange (ASE) for the period 2008-2013. The authors use random effect models to test the hypothesis of this study and extent the analysis to family versus non-family. Findings The study finds a positive relation between CEO’s overconfidence and EM practices in Jordan. Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 111 publications
(155 reference statements)
3
28
0
9
Order By: Relevance
“…For example, Al Qallap (2014) indicated that 26.2 per cent of service companies in Jordan engaged in earnings manipulation, and Abbadi et al (2016) found that companies listed on ASE manipulated their earnings because the average of the DAC was 0.096. Alqatamin et al (2017) documented similar findings with a mean of DAC of 0.097. concluded that the mean of the absolute value of DAC was 9.3 per cent, which indicates that, on an average, the managers of the listed companies on ASE practised earnings management. Finally, Kanakriyah et al (2017) found that public companies in Jordan manipulated the reported earnings at a high level with a mean of 3.772.…”
Section: An Overview Of the Amman Stock Exchangesupporting
confidence: 72%
“…For example, Al Qallap (2014) indicated that 26.2 per cent of service companies in Jordan engaged in earnings manipulation, and Abbadi et al (2016) found that companies listed on ASE manipulated their earnings because the average of the DAC was 0.096. Alqatamin et al (2017) documented similar findings with a mean of DAC of 0.097. concluded that the mean of the absolute value of DAC was 9.3 per cent, which indicates that, on an average, the managers of the listed companies on ASE practised earnings management. Finally, Kanakriyah et al (2017) found that public companies in Jordan manipulated the reported earnings at a high level with a mean of 3.772.…”
Section: An Overview Of the Amman Stock Exchangesupporting
confidence: 72%
“…Earnings management is the ability of the managers to manipulate reported earnings by using discretion in accounting principles. In fact, a well-known process called earnings management is adopted by several executives to manipulate the accounting results of the company through accounting choices and discretionary accruals (Alqatamin et al, 2017). Several studies (DeFond and Jiambalvo, 1994;Healy and Wahlen, 1999;Baker et al, 2009) have proven that managers are encouraged to manage accounting results for several reasons, even though maximizing the value of the company and improving its financial quality are objectives that must be respected by all members of the company.…”
Section: Introductionmentioning
confidence: 99%
“…The entrenchment expresses the will of the CEO to free themselves, totally or at least partially, from the control of the shareholders, while developing specific strategies that allow him or her to achieve the objectives: to increase his/her freedom of action, to improve his/ her discretionary power and to neutralize the various disciplinary mechanisms. Nonetheless, the relationship between a manager's personal characteristics and performance management practices remains ambiguous and controversial (Alqatamin et al, 2017). The purpose of this study is to gain an understanding of whether specific characteristics, such as age, tenure, duality, board membership, gender, compensation, turnover, experience, and nationality, influence earnings management practices.…”
Section: Introductionmentioning
confidence: 99%
“…65 Family firms are much committed to maintaining the long-run sustainability of the firm by avoiding things that can negatively affect the firm. Similarly, Alqatamin, Aribi and Arun 66 revealed that family firms incline to do SEW protection contrary to non-family firms. The reason is that family firms and family firm CEOs with actual control over the management and high access to information on the firm can maximize personal benefits and avoid R&D investment.…”
Section: Family Firm Ceo Overconfidence and Randd Investmentmentioning
confidence: 96%